Role of Radiation Therapy in Adult Extraskeletal Ewing's Sarcoma Patients Treated with Chemotherapy and Surgery. (24th April 2019) - Saiz, Augustine M.; Gingrich, Alicia A.; Canter, Robert J.; Kirane, Amanda R.; Monjazeb, Arta M.; Randall, R. Lor; Thorpe, Steven W.
Abstract : Radiation therapy (RT) is advocated in the multimodal treatment of high-grade soft tissue sarcoma (STS), but its role may be less clear in chemotherapy-sensitive STS such as extraskeletal Ewing sarcoma (EES). The purpose of this study was to determine the role of RT on overall survival (OS) in localized EES adult patients treated with chemotherapy and surgery. Adult patients diagnosed with EES and reported to the National Cancer Database from 2004 to 2014 were evaluated. All patients were treated with surgical resection. Patient demographics, tumor characteristics, treatments received, resection margins, and survival were examined for the 232 patients identified. Using multivariate analysis and Cox proportional hazard analysis, predictors of OS were determined. In the overall cohort, 40 percent of patients received RT and 78 percent received chemotherapy, with 31 percent receiving both. The addition of RT to the patients receiving surgery + chemotherapy did not improve OS (p < 0.05 ). Twenty-four percent of patients who achieved R0 resection after surgery still received RT without any improvement in OS. Patients treated at community cancer centers were more likely to receive additional RT compared with Comprehensive Cancer Centers (p < 0.05 ). In adult EES patients with localized disease treated with chemotherapy and surgery, the addition of RT does not improve overall survival.